Exploring Hybrid Learning Formats in a Nordic Master’s Programme in Visual Studies and Art Education - Buhl, Mie; Hvid Bech Dille, Maria; Hautopp, Heidi; Tervo, Juuso (Proceedings of the International Conference on Networked Learning, 2024)
This paper reports from a project in progress that aims to develop a hybrid learning format that is sufficiently flexible to accommodate collaborative situations between students and teachers on two campuses and in collaborative situations off-campus. The project explores a current co-teaching opportunity that AAU and Aalto University are facing due to the start-up of the new Nordic joint degree master's program Visual Studies and Art Education (NM NoVA). A new physical space has been established at the AAU Copenhagen campus, that digitally facilitates a video-mediated, synchronous learning environment and a similar facilitation is accessible at Aalto University. Teachers and researchers join into a collaboration and conduct the project drawing theoretical knowledge generated in the field of synchronous learning formats and from research in the particular subject related field of digital technology and visual arts education. Furthermore, the project uses the participants’ practical experience from engaging in different synchronous learning formats shared and informed by discussions with peers. Inspired by Design-Based Research (DBR), researchers actively engage in the problem analysis, design, implementation, and analysis of the hybrid learning format. Rich descriptions of the program's evolution are obtained through participant observations, interviews, and a "photo-safari" capturing interactions among students, teachers, and technology. Analytically, the study explores the hybrid format as an enactment of space beyond geographical constraints, drawing inspiration from the concept of "apparatus" within new materialism. Three analytical themes emerge: knowledge-building practices, community-building practices, and longitudinal aspects, providing insights into how the hybrid format impacts collaboration, engagement, and the evolution of educational spaces. Preliminary findings reveal the diverse orientations and pedagogical discussions that emerge within these hybrid spaces, challenging the traditional notion of a "third space" and paving the way for new conceptualisations. The project anticipates further exploration of interdependencies within third spaces and the dynamics of student and teacher bodies within this evolving educational landscape.